Management of dental emergencies amongst Australian general medical practitioners – A case‐vignette study. (19th October 2021) - Park, JS; Page, AT; Shen, P‐H; Price, K; Tennant, M; Kruger, E
Abstract: Background: In Australia, because of inequity in dental service accessibility and affordability, patients can see general medical practitioners (GPs) for acute dental conditions. Methods: This cross‐sectional study consisted of surveys distributed to the board registered GPs practising in Australia. The main outcome measures included statistical analysis of GPs managing different dental emergency scenarios and their confidence and expectations in managing dental emergencies. Results: A total of 425 GPs participated in the study. The sample primarily consisted of GPs practising in metropolitan clinics (n = 315). Most participants reported that they would refer to the dentist for mobilized tooth (n = 402). There was a negative correlation between GPs with 5–29 years of experience and traumatized tooth management ( P  < 0.05). GPs aged between 40 and 49 years were more inclined to treat patients with mobilized teeth [Multivariate (MV): 0.42(0.09–0.74)]. However, GPs with 0–5 years of experience were less likely to manage patients with dental abscess [MV: −0.52(−0.80 to −0.24)]. Conclusion: Most GPs referred dental emergencies to dentists. GP management of dental emergencies were predominantly palliative. Therefore, opportunities for collaborative practice models amongst GPs and dentists may be needed to bridge the gap in the regional and remote locations.